INTERVIEW: FAR SIMULERER - Holmberg, Lars (Tidsskriftet Antropologi, 2001)
The article consists of an interview with a man who has computerised flight simulation as his hobby. In discussing his hobby, he stresses the need for a hobby that has no purpose except the entertainment. From his desktop he simulates actual SAS-flights in Denmark and Europe in real-time. This kind of flight simulation is, in his own words, “as real as it gets”, and that is just the point. The virtual aspect presents him with a predicament, however, since he has a limited amount of spare time in which to fly, and thus he mostly limits himself to shorter flights; the flight from Copenhagen to Aalborg, with an estimated 35 minutes, is his most frequent route.